Urban Youth Identity, Fashion Street, and Place Branding: A Narrative Approach - Media Febriana Sulistyan; Intansari Putriani Sadono; La Mani (Departement of Mathematics Education, 2023)
This article aims to understand place branding through fashion street activities carried out by a group of young people to become the phenomenon, “Citayam Fashion Week,” which was unintentionally held in the Jakarta business district, and the benefits of Citayam Place Branding. It intends to understand Citayam branding through fashion street activities carried out by Citayam youth using semiotic brand analysis with a narrative approach to place branding through online media and social media. The findings in this article focus on the marketing of the Citayam brand. The Citayam Fashion Week activity, which was initially a youth association that created social media content with a fashion show activity on the highway, was able to bring a crowd not only from the residents of Citayam and Jakarta but all the surrounding cities. It spread to several other cities which held similar activities. In addition, this activity is also an opportunity for fashion entrepreneurs to introduce their brands. This study analyzes the place branding strategy and constructs it through viral fashion street activities on social and mass media.